From tensions to synergy: Causation and effectuation in the process of venture creation - Galkina, Tamara; Atkova, Irina; Yang, Man (Strategic Entrepreneurship Journal, 2022)
Abstract Research Summary This article examines previously neglected tensions between causation and effectuation in the process of new venture creation. We studied 41 episodes of new venture creation by entrepreneurs in Finland and Denmark, who we followed applying the diary method. We reveal tense relations between the respective causation and effectuation principles at multiple levels, and identify the corresponding mechanisms for their resolution, which, in turn, lead to the synergy. This study enriches the effectuation research by offering a dynamic perspective on causation‐effectuation interplay and categorizing three modes of their interaction, that is, separation, hybrid synergy, and tensions. Managerial Summary Venture creation is a complex process that involves different decision‐making logics. While combining the goal‐driven logic of causation and non‐goal driven logic of effectuation is essential for the success of a start‐up, the road to their synergy can be paved with different tensions. Our study of 41 episodes of new venture creation by entrepreneurs in Finland and Denmark shows that these tensions can occur at the individual, organizational and inter‐organizational levels. We also show four different mechanisms of how entrepreneurs can overcome these tensions within their ventures and in relations with other stakeholders.